2022
DOI: 10.3390/ani12131639
|View full text |Cite
|
Sign up to set email alerts
|

Oral Palatability Testing of a Medium-Chain Triglyceride Oil Supplement (MCT) in a Cohort of Healthy Dogs in a Non-Clinical Setting

Abstract: The oral palatability of functional foods such as medium-chain triglycerides (MCT) play a crucial role in owner and patient compliance when used as an adjunct in the management of health conditions such as epilepsy. Despite the promising benefits, the palatability of MCT has not undergone a more recent evaluation in dogs. The aim of this study was to assess the palatability and tolerance of short-term, daily supplementation of a 10% metabolic energy based MCT oil volume compared to a tasteless control oil in h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…In accordance with our evidence, Beyen et al [23] reported a total diet consumption in three dogs receiving a diet containing MCT at 11% of ME. In a recent study, Berk et al [36] reported no differences in food intake in 19 healthy dogs when MCT oil was fed at 10% of ME in a short-term (5 day) palatability test.…”
Section: Discussionmentioning
confidence: 96%
“…In accordance with our evidence, Beyen et al [23] reported a total diet consumption in three dogs receiving a diet containing MCT at 11% of ME. In a recent study, Berk et al [36] reported no differences in food intake in 19 healthy dogs when MCT oil was fed at 10% of ME in a short-term (5 day) palatability test.…”
Section: Discussionmentioning
confidence: 96%
“…A dietary inclusion of 0.2% spray-dried A. platensis has been shown to have an immune-stimulation effect as a higher vaccine response and higher levels of fecal IgA were observed in supplemented dogs compared to the control group ( 5 ). Although palatability of nutraceuticals can greatly impact convenience of administration and owner compliance ( 12 ), only scarce studies have assessed the palatability of microalgae supplemented diets.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the palatability of such products has not been evaluated in pets. In the case of nutraceutical agents, palatability can have a major influence on the convenience of administration, which has an impact on both patient and owner compliance [ 29 ]. The authors’ hypothesis is that the palatability of Spirulina tablets in dogs and cats may be correlated with the daily amounts administered, with higher amounts leading to a decrease in palatability; additionally, the authors hypothesize that the owners’ evaluation of such supplementation will be positive and that the owners will not report negative changes in the health evaluation of their pet caused by Spirulina supplementation, such as increasing episodes of vomiting or diarrhea, and may instead notice positive effects, namely improvements in coat condition and physical activity levels of their pets.…”
Section: Introductionmentioning
confidence: 99%